Bioprospecção de bactérias cultiváveis isoladas de Anopheles darlingi Root, 1926 para o controle da malária por paratransgênese - Serrão, Deidre Machado (2019)
Mosquitoes of the genus Anopheles Meigan, 1818 are the main vectors of parasites that cause human malaria, a disease of global medical importance that also affects the economies of many countries. In Brazil, the most prevalent vector is Anopheles darlingi Root, 1926, whose female is highly susceptible to infection by the protozoan Plasmodium vivax Grassi and Feletti, 1890, responsible for most cases recorded in the Brazilian Amazon. Despite numerous advances worldwide, through strategies of vector control, early diagnosis and treatment, malaria still constitutes a serious public health problem. In this scenario, an alternative that presents great potential in the fight against malaria and other vector diseases is paratransgenesis, a method that uses genetically modified symbiotic bacteria as conductors of antiparasitic molecules. However, for the success of the paratransgenia, the microorganisms used must have constant association with the vector, being able to be transmitted vertically, horizontally and transestationally, besides being cultivable, susceptible of genetic manipulation and not pathogenic to humans. In view of the above and taking into account the scarce work related to the transmission of bacteria in A. darlingi, as well as the composition of its microbiota, this work had the objective to select cultivable bacteria, which present characteristics of vertical transmission in A. darlingi, to be used in the control of malaria, through paratransgenic approaches. For this, bacterial isolation was performed, morphological characterization and molecular identification by the 16S rRNA gene of bacteria isolated from ovaries of A. darlingi adult mosquitoes collected in a periurban area of Manaus, as well as their eggs, larvae and ovaries of mosquitoes born in the laboratory. Four identified bacterial species were also tested to verify their transformation potential by the electroporation method. The results obtained demonstrated that of the 176 bacteria isolated, 62 identified corresponded to the phyla: Proteobacteria, Bacteroidetes, Actinobacteria and Firmicutes, with two predominant genera, Acinetobacter and Enterobacter. By molecular analysis it was also possible to detect six genera detected for the first time in A. darlingi: Elizabethkingia, Cupriavidus, Leucobacter, Pectobacterium, Rhizobium and Nubsella. The species that presented signs of vertical transmission in the mosquito studied were: Acinetobacter bereziniae, Enterobacter asburiae and Serratia marcescens, the latter being the one with the best potential for transformation with the plasmid pKS1-GFP, which expresses the GFP fluorescent protein, useful for future tests of monitoring in A. darlingi. Key words: symbiotic bacteria, paratransgenesis, transmission blockade, malaria, Amazon.